1999
DOI: 10.1002/(sici)1098-1136(19990201)25:3<229::aid-glia3>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Ability of retinal M�ller glial cells to protect neurons against excitotoxicity in vitro depends upon maturation and neuron-glial interactions

Abstract: Glutamate is the most abundant excitatory amino acid in the central nervous system. It has also been described as a potent toxin when present in high concentrations because excessive stimulation of its receptors leads to neuronal death. Glial influence on neuronal survival has already been shown in the central nervous system, but the mechanisms underlying glial neuroprotection are only partly known. When cells isolated from newborn rat retina were maintained in culture as enriched neuronal populations, 80% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…20 Another possibility may be the lack of neuron-glial interactions in the present study. Heidinger et al 22 showed a paradoxical response of cultured Müller cells to excitotoxic amino acids: glutamine synthetase activity in pure Müller cell cultures was not increased by glutamine application, whereas the activity was upregulated by glutamine in a mixture of neuron/glial cultures. This would indicate that intimate interconnections of Müller cells with retinal neurons appear to be necessary to yield high expression levels of glutamine synthetase in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another possibility may be the lack of neuron-glial interactions in the present study. Heidinger et al 22 showed a paradoxical response of cultured Müller cells to excitotoxic amino acids: glutamine synthetase activity in pure Müller cell cultures was not increased by glutamine application, whereas the activity was upregulated by glutamine in a mixture of neuron/glial cultures. This would indicate that intimate interconnections of Müller cells with retinal neurons appear to be necessary to yield high expression levels of glutamine synthetase in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Slit's ability to protect against neuronal injury in this model, the first demonstration of its kind that we are aware of, must result from Slit-mediated signaling of cytoprotective pathways in glia and/or neurons independent of any reduction in leukocyte chemotaxis. Although further studies are required to elucidate the mechanistic basis for the observed protective effect, a direct effect of Slit that improves the glial response to ischemia is possible, since the ability of glial cells to promote neuronal viability in the setting of ischemia is well established (Lee et al, 2004;Rosenberg et al, 1989;Heidinger et al, 1999;Trendelenburg et al, 2005;Swanson et al, 2004). In Drosophila, glial Slit receptors play an important role in neuron-glia interactions by influencing the survival and migration of both cell types; moreover, interfering with these interactions alters their responsiveness to Slit-Robo signaling (Kinrade et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Cultured neurons are more vulnerable to the potential neurotoxicity of corticosterone when few glial cells are present in this culture (Dugan et al, 1995;Lewis et al, 1998). For example, when neuronal cells isolated form newborn rat were maintained in culture as enriched neuronal populations, 80% of the cells were killed by application of excitotoxic concentrations of glutamate and this neuronal death was not observed in mixed neuron/glial cultures (Heidinger et al, 1999). …”
mentioning
confidence: 99%